TEACHING AND LEARNING ACTIVITIES DURING THE IMPLEMENTATION OF KURIKULUM MERDEKA IN JUNIOR HIGH SCHOOL - Cahyani, Putu Novi Trisna; Artini, Luh Putu; Santosa, Made Hery (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study aims to determine teaching and learning activities on the implementation of Kurikulum Merdeka.  This study uses a mixed approach with descriptive methods.  The population of this study was 7th grade English teachers totaling 2 people and 301 class VII students.  The research sample used was the Probability Sampling Technique, namely simple random sampling with an error rate of 5%, so the number of samples in this study became 172 students and 2 English teachers.  Data collection techniques used in this study were documents, observations, and questionnaires.  Based on the results of the research, it shows that the activities contained in the Kurikulum Merdeka module can accommodate students' competencies and skills.  Therefore, it is very clear that teachers need to create modules for teaching guidelines.  The results shown in the learning activities in the classroom in the teacher module have not been fully implemented by the teacher in the classroom.  The teacher makes activities according to the class atmosphere.  The perception of the teachers is included in the category of positive perceptions because, in the implementation of Kurikulum Merdeka, there are activities that can foster students' enthusiasm for comfort while learning in the classroom in Kurikulum Merdeka learning and are shown with very high results seen from the average overall statement of 89%. Meanwhile, from the students side, it has a positive perception of the media that the teacher uses to convey teaching materials and in the learning process makes students think critically.  This is evidenced by the responses of respondents with an average of 77.2%.